Cognitive style and working memory among adolescents with specific learning disability - Monica Daniel; Romate John; Eslavath Rajkumar; Allen Joshua George; John Abraham (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: In a world where education directly influences the quality of life of an individual, educational handicaps are a grave issue that plagues the lives of those affected. The current study aims to find out whether there is a difference in the cognitive style and working memory capacity among adolescents with specific learning disability (SLD) in comparison to their age-matched equivalent group without SLD. The study also targets to find out if there exists any relationship between cognitive style and working memory. MATERIALS AND METHODS: A total of sixty participants were selected (thirty adolescents with learning disability and thirty age-matched adolescents without learning disability) from Bangalore district of Karnataka and Thrissur district of Kerala using purposive sampling method. The tools used were the Indian adaptation of Embedded Figures Test by Nigam (1997) and the Wechsler Intelligence Scale for Children-Fourth Edition by Wechsler (2003). RESULTS: The results showed that there exists a significant difference in cognitive style dimensions of field dependence and independence between adolescents with learning disability (M = 11.6, standard deviation [SD] = 6.52) and adolescents without learning disability (M = 25.2, SD = 7.33) as well as in the working memory capacity between adolescents with learning disability (M = 66.7, SD = 19.26) and adolescents without learning disability (M = 102, SD = 14.93) groups under study (p < 0.01). The results also indicate that there exists no significant relationship between cognitive style and working memory. CONCLUSION: Adolescents with SLD was found to be field dependent and has low working memory capacity than adolescents without learning disability. The results reflect the need for developing cognitive interventions to enhance working memory capacity and cognitive style for helping adolescents with learning disability in all areas of their functioning, such that the society benefits as a whole.